COMPARATIVE STUDY OF NEW DRUG OF LONG ACTING METOPROLOL TARTRATE - EGILOK RETARD AND ORIGINAL DRUG OF METOPROLOL SUCCINATE – BETALOC ZOK IN PATIENTS WITH MILD TO MODERATE ARTERIAL HYPERTENSION - J. V. Lukina; A. D. Deev; N. A. Dmitrieva; N. Y. Ivanenkova; A. A. Serazhim; G. F. Andreeva; S. Y. Martsevich (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To study efficiency and safety of new drug of long acting metoprolol tartrate, “Egilok retard” (ER) in patients with mild to moderate arterial hypertension (AH) in comparison with the original drug of metoprolol succinat, “Betaloc ZOK” (BZ), possibility of reaching target blood pressure (BP) level with treatment with each drug. Material and methods. 30 patients (11 men and 19 women) with mild to moderate AH took part in randomized, open, cross over study. Previous antihypertensive treatment had been canceled for all the patients 10-14 days before the study started. Each patient by turns was treated during 6 weeks with ER and BZ 50-100 mg daily. After cancellation of the previous antihypertensive therapy, BZ and ER were prescribed (according to the randomization table) in dose 50 mg daily. Drugs were taken once per day. 29 patients completed therapy with the first drug of randomization, 25 patients – with the second. After 2 weeks efficiency of treatment was assessed by target BP level achievement (< 140/90 mmHg). If efficiency of beta-adrenoblocker (BB) was not sufficient, the dose of the drug was doubled to 100 mg daily, if target level was reached – the dose remained unchanged. Treatment with the settled dose was held within next 4 weeks. After 6-week treatment with the first randomized drug antihypertensive therapy was canceled for 10-14 days depending on the BB dose. At each visit office BP and heart rate were assessed, EKG was registered. Side-effects were registered according to the self-control diary, questionnaire results, examination and EKG data. Results. After 6-week treatment with ER and BZ average level of systolic BP reduced by 15,7 and 15,2 mmHg, of diastolic BP – by 8,0 and 4,5 mmHg, heart rate – by 4,1 and 4,3 beat/min respectively. Differences between antihypertensive and heart rate lowering effect of the studied drugs were not significant. Target BP level with treatment with both drugs was reached in approximately half cases – in 48% of BZ patients, and in 56% of ER patients. Biger number of side effects was registered in BZ treatment (p=0,03). Most side effects were not severe and according to the patient assessment tolerance of both drugs didn’t differ. Conclusion. Results of the study show that in patients with mild to moderate AH 6-week monotherapy with new drug of long acting metoprolol tartrate, ER, does not differ on efficacy and safety from original drug of long acting metoprolol succinate, BZ.